Transformation of fishermen in Bangko sub-district, Rokan Hilir: Analysis of fishermen’s perceptions toward fisheries modernization - Metalisa Rindi; Arief Hazmi; Willy Yanti Chicka; Rosmalinda Indriana Inke (BIO Web of Conferences)
Fisheries modernization is one of the efforts to improve the welfare of fishermen and the sustainability of fishery resources. The success of implementing modernization in fisheries is highly dependent on the perception and acceptance of fishermen towards these changes. The study aimed to analyze fishermen’s perceptions of the modernization of fishing in the Bangko sub-district Rokan Hilir. This study involved 30 respondents and used a quantitative research method with a survey approach. The data collection technique used is interviews using questionnaires, observations, and documentation. Fisherman transformation in the context of fisheries modernization refers to changes that occur to fishermen in the use of equipment technology, access to information, institutional support, and influence on conductivity. The study’s findings indicate that there needs to be more awareness of the modernization of fisheries among fishermen. Juragan fishermen realize fisheries’ modernization, while traditional fishermen still need to be higher in realizing fisheries’ modernization.